Optimising chip placement sequence in SMT operation using C++ - Chua, Jyh Huey. (2010)
This dissertation covers the development of a PC window based optimization component placement system (WinCPS) using C++. Optimization of printed circuit board (PCB) component insertion/placement operations is currently a popular research area and an increasing number of solution approaches have been proposed. The area of work here is focused on the popular and sophisticated multi-head concurrent operation machine (MCO) for surface mounted devices (SMD) in the printed circuit broad industry.